Burn Bright an Alpha and Omega Novel - Briggs, Patricia (New York Ace, 2018)
They are the wild and the broken. The werewolves too damaged to live safely among their own kind. For their own good, they have been exiled to the outskirts of Aspen Creek, Montana. Close enough to the Marrok's pack to have its support; far enough away to not cause any harm. With their Alpha out of the country, Charles and Anna are on call when an SOS comes in from the fae mate of one such wildling. Heading into the mountainous wilderness, they interrupt the abduction of the wolf -- but can't stop blood from being shed. Now Charles and Anna must use their skills -- his as enforcer, hers as peacemaker-- to track down the attackers, reopening a painful chapter in the past that springs from the darkest magic of the witchborn.
105996
Keywords: Werewolves -- Fiction; Exiles -- Fiction; Magic -- Fiction; Fantasy -- Fiction -- Urban Life; Montana -- Fiction; Paranormal fiction; Occult fiction; Fiction